Organizacja, struktura oraz działanie ruchu anty- i alterglobalizacyjnego w państwach Unii Europejskiej - Miliszewski, Kamil (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
This paper discusses the main notions of the theory of organization and operation of a social movement that has been termed the anti-, and alter-globalization movement since the late 1990s. Its beginnings can be found in the protests of the populations of both Americas, mainly those of Mexico and the US, against a free-trade zone and agreements of states with international organizations. Attention should be paid to the structures the movement has built in European Union states, most closely related to globalization processes. Here both formal structures are encountered, such as the non-government organization Attac, and informal organizations operating on the principles of direct democracy. Formal organizations formulate legal and legitimate statutes and attempt to discuss the issues of globalization at the level of public debate. This is the path chosen by the parties of the so-called ‘new politics’ – prophetic, left-wing and libertarian parties. Informal organizations usually operate along principles of direct action and dialogue inside the movement itself. The key role in the shaping of the organizational structures of the anti-, and alter-globalization movements in Europe is played by the international European Social Forum, which is the venue for annual meetings and debates of different ideological currents.